Dispensasi Kawin Akibat Hamil Pra-nikah Menurut Perspektif Imam Syafi’i dan Imam Hanafi (Studi Putusan Pengadilan Agama Kabupaten Malang Nomor 0486/Pdt.P/2021/PA.Kab.Mlg) - Pitria Nur Rinawati; Ibn Jazari; Ahmad Subekti (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
The phenomenon of getting pregnant out of wedlock is one of the factors in submitting an application for a marriage dispensation at the Religious Courts. Marriage dispensation is an allowance given to prospective husband and wife who have not reached the minimum age limit regulated in the marriage law. From the context of the research above, the researcher makes the conception of Islamic law regarding marriage dispensation, considerations of religious court judges in deciding cases of marriage dispensation number 0486/Pdt.P/2021/PA.Kab.Mlg and analyzes judge’s decison number 0486/Pdt.P/2021/PA.Kab.Mlg based on the perspective of Imam Syafi’i and Imam Hanafi as the focus of research that will be studied in this study. As in this research process, the researcher uses research methods, in which the research method used is a qualitative approach method and the type of legal juridical normative research. In collecting data, researchers used the interview method, namely using structured interview and researchers also used the documentation method to find data. The dokumentation used is in the form of decisions to be reviewed, books, journals. The results of this study are that Islam does not regulate the age limit for marriage. Then Imam Syafi’i and Imam Hanafi also allow at what age a person can get married, but he recommends marriage should ideally be done when someone has reached puberty. In the decision reviewed by the researcher, the judge in deciding the case number 0486/Pdt.P/2021/PA.Kab.Mlg used the legal basic for the KHI Article 53.